Glycemic Control in Diabetes Type 2 Patients in Foster Families of Brod-Posavina County During the COVID-19 Pandemic : Kontrola glikemije u bolesnika s dijabetesom tipa 2 u udomiteljskim obiteljima Brodsko-posavske županije tijekom pandemije COVID-19 - Miškić, Blaženka (Array, 2021)
COVID-19 pandemic has changed everyday life and medical supervision of chronically ill patients. Epidemiological measures, social distancing, and limited access to medical care impair glycemic control in patients with diabetes. Also, type 2 diabetes is a risk factor for more severe form of coronavirus disease. A large proportion of diabetic patients are placed in foster families who also adapt to the new situation. The purpose of this study was to examine the manner and frequency of glycemic control in patients with type 2 diabetes who are placed in foster families in the region of Brod- Posavina County. We established contact with patients suffering from type 2 diabetes situated in foster families and their caregivers. Measurement of glycemia was performed several times a day with regular notes and the data were supplemented by an insight into the medical documentation of patients in the hospital information system. The study included 33 patients with type 2 diabetes. The relationship between HbA1C with fasting and postprandial glycemia was linear. There were no statistically significant differences in HbA1C regulation by type of therapy. There was a significant difference in the number of complications according to the level of HbA1C (Hi square test = 25.982, p